STUDY OF FISSION GAS BUBBLES AND INTERACTION LAYER ON IRRADIATED U3Si2-Al DENSITY OF 4.8 gU/cm3 - Juan Carlos Sihotang; Maman Kartaman Ajiriyanto; Anditania Sari Dwi Putri; Ely Nurlaily; Junaedi Junaedi; Aslina Br Ginting; Supardjo Supardjo (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2022)
STUDY OF FISSION GAS BUBBLES AND INTERACTION LAYER ON IRRADIATED U3Si2-Al DENSITY OF 4.8 gU/cm3. Uranium-silicide compound fuel dispersed in aluminium matrix (U3Si2-Al) have been used in a large number of research reactors around the world because of its excellent behavior under irradiation. This fuel also provides high uranium density with typical fuel loading up to 4.8 gU/cm3 to compensate for the reduced fissile amount in LEU. To improve the density of current U3Si2-Al (2.96 gU/cm3) used in Indonesian GA Siwabessy Multipurpose Research Reactor, U3Si2-Al dispersion fuel plate with density of 4.8 gU/cm3 (U235 ∼19.75%) had been irradiated in RSG GAS for 175 days at 15 MW power to burnup level of approximately 40%. The characterization was performed using SEM-EDS and optical microscope to study microstructure of the irradiatted fuel, largely the fission gas bubbles and the interaction layer between U3Si2 fuel and Al matrix. The average diameter of the bubbles with diameter from 0.06 to 0.55 µm was 0.21 µm. The interaction layer was identified as U(Al,Si)2,3 with thickness of approximately 1.5 µm. The relatively small fission gas bubbles and the interaction layer didn’t cause swelling on the fuel and the overall performance of the fuel plate was very good.Keyword:  LEU, uranium-silicide, post-irradiation examination, interaction layer, fission gas bubbles.